PERAN KELOMPOK TANI DAN ANGGOTA PADA PENERAPAN INOVASI TEKNOLOGI PERTANIAN DI DESA TRIMULYO - Ismiasih Ismiasih; Siwi Istiana Dinarti; Mega Winda Adnanti (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
The agriculture sector is one of the leading sectors that plays an important role in supporting the county’s economy. However, the main problems in the agricultural sector today are the decline in land area and quality of human resources, limited fasilities such as farmer capital, equipment and technology support and agricultural institutions. The aims of this study was to determine the role of farmer groups and farmer members in the application of tecnological innovations in farming. The research method used is descriptive qualitative using a likert scale to analyze the role of groups and members of farmers. Members and administrator’s group were used as our research sample. The results showed that the roles of farmer groups were grouped into three categories, they were very instrumental in providing services, playing a role in the field of business, and palying a role in assiting agricultural technology innovation. Meanwhile, the role of members in the application of agricultural technology is quite instrumental.